VACUNAS EXTORSIVAS COMO MEDIO DESESTABILIZANTE DE LA ECONOMIA DEL SECTOR COMERCIAL EN EL ECUADOR - Bravo León, Erika Fernanda (2024)
This Curricular Integration Work is entitled "Extortive Vaccines as a destabilizing means of the economy of the commercial sector in Ecuador", it was carried out because the criminal practice known as extortive vaccines have become a growing concern in the commercial sector of Ecuador. In this context we can see that, given the large increase in extortion, the State has not implemented actions to ensure human security as well as the fact that Ecuadorian traders can not work safely and calmly, which has caused economic losses. This is why the problem of this study arises. This study shows how the increase in the crime of extortion represents a threat to the economy of the commercial sector, as it has generated fear and insecurity to traders, as well as economic losses, unemployment, business closures, migration, so it is necessary that the State as the main protector to ensure first the rights of traders against insecurity and second to implement actions to help reduce the commission of this crime. Based on this problem and for its development, several research materials such as books, magazines and physical and digital dictionaries, national and comparative legislations, which have been used throughout this work, were collected. Methods such as scientific, deductive, inductive, statistical and comparative were also used. Statistical and comparative methods were also used, as well as techniques such as surveys and interviews, the results of which were essential to be able to propose guidelines to ensure security and at the same time maintain a stable economy in the commercial sector.